Reader Response: Timing and Impact of Psychiatric, Cognitive, and Motor Abnormalities in Huntington Disease. (22nd March 2022) - Bird, Thomas D.; Lange, Herwig; Cruickshank, Travis; Dose, Matthias; Eddy, Clare; Oosterloo, Mayke; Paulsen, Jane S.; Reilmann, Ralf; Rickards, Hugh; Roos, Raymund A.C.; Weindl, Adolf
Abstract : McAllister et al. 1 made an important contribution to knowledge of Huntington disease (HD), finding that 42% of >6, 000 persons with HD have onset of a psychiatric or cognitive symptom before motor symptoms, and these nonmotor symptoms can be functionally debilitating. Their conclusion that "nonmotor symptoms should not be used to make a clinical diagnosis of HD, " 1 due to their common frequency in the general population, seems excessively broad and negative. Certainly, one should be cautious and not use depression as a diagnostic factor. However, our clinical experience indicates that psychiatric, behavioral, or cognitive symptoms should play a diagnostic role in patients with a positive genetic test.